Enhancing collaborative learning in flipped classroom - Halili, S.H.; Abdul Razak, R.; Zainuddin, Z. (2014)
With the advent of technology Web 2.0, two ways communication can be established among the learners in teaching and learning activities. The learners can study collaboratively with others even in different location and different time. Flipped classroom is the opposite of traditional learning where the learners watch lectures video outside the classroom and conduct interactive discussion in the classroom. After reviewing several articles, it shows that the application of flipped classroom can enhance a collaborative learning for students' learning activities. However, some challenges might potentially happened such as not all learners wish to work together, not all of them have selfdirected learning skill and the teachers need more trainings before implementing flipped classroom.